2011
DOI: 10.1093/humrep/der322
|View full text |Cite
|
Sign up to set email alerts
|

Risk of borderline and invasive ovarian tumours after ovarian stimulation for in vitro fertilization in a large Dutch cohort

Abstract: BACKGROUNDLong-term effects of ovarian stimulation for IVF on the risk of ovarian malignancies are unknown.METHODSWe identified a nationwide historic cohort of 19 146 women who received IVF treatment in the Netherlands between 1983 and 1995, and a comparison group of 6006 subfertile women not treated with IVF. In 1997–1999, data on reproductive risk factors were obtained from 65% of women and data on subfertility (treatment) were obtained from the medical records. The incidence of ovarian malignancies (includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
3
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(152 citation statements)
references
References 44 publications
6
131
3
4
Order By: Relevance
“…In particular, there are studies showing no protective effect of hormonal contraceptives against BOTs as opposed to ovarian cancers [3,7]; however, the results of further studies concerning BOTs and hormonal contraceptives are controversial, as discussed later. The increased risk of BOTs may also be associated with the use of fertility drugs [8].…”
Section: Epidemiologymentioning
confidence: 99%
“…In particular, there are studies showing no protective effect of hormonal contraceptives against BOTs as opposed to ovarian cancers [3,7]; however, the results of further studies concerning BOTs and hormonal contraceptives are controversial, as discussed later. The increased risk of BOTs may also be associated with the use of fertility drugs [8].…”
Section: Epidemiologymentioning
confidence: 99%
“…By considering that human ovarian carcinoma tissues have an estimated +46 % of cyclin D1 overexpression, that has been correlated with an ascending clinical stage and poor prognosis [37], we can hypothesize that such a more limited increase might highlight a latent precursor phase, that predisposes to potential cancer development. Indeed, epidemiological data evidenced an increased risk for borderline ovarian tumors in infertile women treated with IVF [10], and it is noteworthy that about 2/3 of serous borderline ovarian tumors are characterized by kras mutations that determines a significant increase of cyclin D1 expression [38]. On the other hand, we cannot exclude the possibility that, in our experimental model, cyclin D1 increase could be a hypertrophic response of epithelial cells of the FT to supraphysiological gonadotropin stimulation, without any established role in the causation of OC.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, infertility per se increases the risk for OC [4], and nulliparous women or women who used fertility drugs to achieve pregnancy seem to have a higher risk of developing OC than women with children and/or those that have used oral contraceptives [8]. Large epidemiological studies evidenced a weak but not significant association between infertility drugs and OC risk [5,[9][10][11], even if an increased risk of borderline ovarian tumors in IVF groups compared with the general population has been reported [10]. As a consequence, it is necessary to evaluate how the need of motherhood could reconcile with the side effects of these therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Th is was further supported by publications from Whittemore et al (1992) and Rossing et al (1994) in which the use of gonadotrophins and clomiphene were implicated. Subsequent analyses (Venn et al 1995(Venn et al , 1999Klip et al 2000) including one with the editor ' s collaborators (dos Santos Silva et al 2009) could not fi nd an increased incidence or mortality from ovarian cancer among women with infertility or aft er ovarian/ovulation stimulation, although a most recent report from the Dutch group (van Leeuwen et al 2011) describes an increased risk of borderline and invasive ovarian tumours aft er ovarian stimulation for in vitro fertilisation.…”
Section: Editorialmentioning
confidence: 99%
“…Th ey were reported by Rossing et al (1994) among women with ovarian tumours following treatment with clomiphene, and the review by Ness et al (2002) of eight case -control studies demonstrated an increased incidence of borderline tumours among nulligravid women who had used fertility drugs. Th e study by van Leeuwen et al (2011) reported fi nding borderline tumours in women who had undergone IVF. Th e report by Menon et al (2009) suggests these tumours are more likely to be detected among women undergoing ultrasound screening as compared with those in their multimodal screening group.…”
Section: Editorialmentioning
confidence: 99%